Pelatihan Keterampilan Usaha Produktif Bidang Jahit Dasar Pembuatan Blus Pada Busana Casual di Balatkop - Ariyana Damayanti (ABDI KARYA : Pengabdian Kepada Masyarakat, 2024)
Mentoring training can be chosen as an alternative because of the large number of fashion industries in Central Java and business opportunities in the fashion sector, considering that clothing is a basic human need. So the opportunity to get a job in this field is very high. The training that will be given is making casual clothing consisting of a top in the form of a blouse and a bottom in the form of a skirt. The technique for making casual clothing, the process begins with taking correct body measurements, making basic patterns for the front and back of the body, both skirts and blouses, breaking up the pattern according to the design, process cutting material, sewing process and finishing process. It is this series of manufacturing processes that will produce good quality clothing, so that later with this skill, people can further develop it as initial capital in opening a business in the field of clothing sewing. This training aims to provide additional knowledge to participants in the field of clothing making. This training is expected to be able to add new experiences so as to improve the skills and competencies of participants. The methods used include the interactive method, demonstration method, and question and answer method. This training produces casual clothing and participants can master the process of measuring clothing, pattern making and clothing sewing techniques